Mathematical Representation Ability in View of Self-Efficacy: Systematic Literature Review - Lutfi, Jasmine Salsabila; Dasari, Dadan (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
One of the psychological aspects of students that encourages students' mathematical representation abilities is self-efficacy. This article is a Systematic Literature Review (SLR) of 22 research published until October 2022 with the help of the Publish or Perish (PoP) application with the Scopus, and Google Scholar databases. SLR can be useful for finding research gaps from previous research. This article aims to; (1) investigate the period, index, research approach, subject matter, and subject demographics heterogeneity from 22 inclusion articles, (2) description of mathematical representation abilities in terms of self-efficacy, and (3) learning methods/approaches/strategies that can enhance self-efficacy, as well as the ability of mathematical representation. The results of the SLR research show that students with low self-efficacy have limitations in mathematical representations such as the majority involving a single representation, difficulty understanding the meaning of the questions, and lack understanding of material concepts. The ability of students' mathematical representation with moderate levels of self-efficacy experienced several problems such as difficult to solve problems, less accurate calculations, and dominantly showed moderate mathematical representation abilities. Meanwhile, students with dominant high self-efficacy also show high mathematical representation abilities. For future researchers, it is recommended to conduct research on this topic at the elementary school level, research locations outside Java Island, as well as trigonometry material.